Kajian Unsur Tanah Jarang (LTJ) Pada Lahan Bekas Tambang Timah dan Tambang Kaolin Kecamatan Merawang Kabupaten Bangka - Delita Ega Andini; Guskarnali Guskarnali; Alfitri Rosita (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2019)
Indonesia have natural resources in producing rare earth elements (REE). The abundance ofmineral resources in Bangka Island is related to the strategic geological position of BangkaIsland formed on the Southeast Asian Tin Belt (Cobbing, 2005). Geologically, the REEdeposits are associated with acid rocks (granitic) and phosphatic deposits. This studyfocuses on primary samples taken directly from ex tin mining area and ex kaolin mining inMerawang District, Bangka. The analysis of the sample uses X-Ray Fluorescence (XRF) tofind out the REE content are Ce, La, Nd, Sb, Sc, Sm, Te, Th, Y, and U. The analysis resultsshow that the spread of elemental content in the sample tends to have a relatively similarpresence. But in Sample 1 shows the Ce element is the dominant element that is equal to25.19 ppm, equivalent to 0.002% of its availability in sedimentary sand in the ex tin mining.while on the ex kaoline mining area the results of the analysis showed that there wasThorium (Th) content in Sample 3 of 70.05 ppm or 0.007% and was the highest contentcompared to other elements in all samples.